Design and Performance Evaluation of an IoT-Based Automatic Airflow Control System for a PV/T Solar Dryer with Silica Gel Adsorption Heat Storage - Putri Arsyafdini Oktavionry; Leopold Oscar Nelwan; I Dewa Made Subrata (The University of Lampung, 2026)
Solar energy is one of the most promising renewable energy sources, yet solar drying operating costs often remain prohibitive for small-scale farming. This research aims to design and evaluate the performance of an automated air flow control system for a PV/T collector integrated with an adsorption channel. The methodology focuses on developing a real-time monitoring and control logic based on environmental parameters. The system utilizes a microcontroller-based unit for data acquisition of temperature and humidity, coupled with a high-torque motor actuation system to regulate valve positioning between the collector and the desiccant unit. Results indicate that the control system manages air distribution effectively across a temperature control range of 40 °C to 4 3°C. The system demonstrated high responsiveness with a mechanical actuation speed of 3 seconds for a full 90-degree valve rotation. During the adsorption phase, the silica gel's moisture content rose from 23.57% to 27.38%. Furthermore, the silica gel adsorption unit contributed to thermal stability by maintaining a temperature gradient of 3-7 °C between the plenum and the environment, effectively recycling adsorption heat to enhance the drying air temperature even during low solar radiation.